Synthesis of catalytically active porous platinum nanoparticles by transmetallation reaction and proposition of the mechanism - Pasricha, Renu; Bala, Tanushree; Biradar, Ankush V.; Shubhangi B. Umbarkar; Sastry, Murali (Small, 2009)
A facile method for the synthesis of porous platinum nanoparticles by transmetallation reactions between sacrificial nickel nanoparticles and chloroplatinic acid (H(2)PtCl(6)) in solution, as well as at the constrained environment of the air water interface, using a Langmuir-Blodgett instrumental setup is presented. To carry out the transmetallation at the air-water interface hydrophobized nickel nanoparticles are assembled as a monolayer on the sub phase containing platinum ions. The porous Pt nanoparticles obtained as a result of the reaction are found to act as extremely good catalysts for hydrogenation reaction. The products are well characterized by TEM, HRTEM, EDAX, and STEM. Attempts are made to postulate the plausible mechanism of this reaction to generate this kind of nanoparticle with controllable geometric shape and structure. This simple strategy has the potential to synthesize other nanomaterials of interest too.
Keywords: Catalysts; Interfaces; Nickel nanoparticles; porous platinum; Transmetallation

Template-assisted synthesis and characterization of passivated nickel nanoparticles - Gopalan, E. Veena; Malini, K. A.; Santhoshkumar, G.; Narayanan, T. N.; Joy, Pattayil Alias; Al-Omari, I. A.; Kumar, D. Sakthi; Yoshida, Yasuhiko; Anantharaman, Maliemadom R. (Nanoscale Research Letters, 2010)
Potential applications of nickel nanoparticles demand the synthesis of self-protected nickel nanoparticles by different synthesis techniques. A novel and simple technique for the synthesis of self-protected nickel nanoparticles is realized by the inter-matrix synthesis of nickel nanoparticles by cation exchange reduction in two types of resins. Two different polymer templates namely strongly acidic cation exchange resins and weakly acidic cation exchange resins provided with cation exchange sites which can anchor metal cations by the ion exchange process are used. The nickel ions which are held at the cation exchange sites by ion fixation can be subsequently reduced to metal nanoparticles by using sodium borohydride as the reducing agent. The composites are cycled repeating the loading reduction cycle involved in the synthesis procedure. X-Ray Diffraction, Scanning Electron Microscopy, Transmission Electron microscopy, Energy Dispersive Spectrum, and Inductively Coupled Plasma Analysis are effectively utilized to investigate the different structural characteristics of the nanocomposites. The hysteresis loop parameters namely saturation magnetization and coercivity are measured using Vibrating Sample Magnetometer. The thermomagnetization study is also conducted to evaluate the Curie temperature values of the composites. The effect of cycling on the structural and magnetic characteristics of the two composites are dealt in detail. A comparison between the different characteristics of the two nanocomposites is also provided.
Keywords: Nickel nanoparticles; Polymer-metal nanocomposites; Strongly acidic cation exchange resin; Stuctural and magnetic properties; Weakly acidic cation exchange resin